PERANCANGAN PERANGKAT PEMBELAJARAN MATA PELAJARAN MATEMATIKA PEKET C SETARA SMA - EKA PASCA SURYA BAYU (Inovasi Pendidikan, 2017)
Equal Education Package C equivalent SMA is one of the government-designed programs to reduce the number of school dropouts in Indonesia. If viewed from the duration of education pursued by the Indonesian people based on the gross enrollment rate and the net enrollment rate, obtained on average only until high school education. One of the program implementers of Package C is PKBM Kasih Bundo, but this education unit has not designed the learning with reference credit unit of competence (SKK), so there is no integration between the content standard with the standard process in its implementation. The purpose of this research is to improve the competence of tutors in designing curriculum devoted to annual program and semester program by reviewing standard of content and standard of non formal education process through workshop activity. The type of research used is descriptive qualitative where the results of the research will be described without changing the information obtained during the study took place. The data obtained is the data during KKG-TK activities took place using triangulation. The results obtained that this activity can improve the ability of tutors in the preparation of annual programs and semester program by mapping SKK in the form of face-to-face, tutorial, and independent.Keywords: Non Formal Education Package Equality C, Content Standards, Process Standards